Colorimetric Carbonyl Sulfide (COS)/Hydrogen Sulfide (H2S) Donation from γ‐Ketothiocarbamate Donor Motifs. (4th September 2018) - Zhao, Yu; Steiger, Andrea K.; Pluth, Michael D.
Abstract: Hydrogen sulfide (H2 S) is a biologically active molecule that exhibits protective effects in a variety of physiological and pathological processes. Although several H2 S‐related biological effects have been discovered by using H2 S donors, knowing how much H2 S has been released from donors under different conditions remains challenging. Now, a series of γ‐ketothiocarbamate (γ‐KetoTCM) compounds that provide the first examples of colorimetric H2 S donors and enable direct quantification of H2 S release, were reported. These compounds are activated through a pH‐dependent deprotonation/β‐elimination sequence to release carbonyl sulfide (COS), which is quickly converted into H2 S by carbonic anhydrase. The p ‐nitroaniline released upon donor activation provides an optical readout that correlates directly to COS/H2 S release, thus enabling colorimetric measurement of H2 S donation. Abstract : H2 S ist ein wichtiges Biomolekül : Ein kolorimetrischer H2 S‐Donor wurde entwickelt, der H2 S als Antwort auf eine Sequenz aus Deprotonierung und β‐Eliminierung abgibt. Das bei der Aktivierung entstehende p ‐Nitroanilin dient als optischer Indikator, sodass die H2 S‐Freisetzung direkt während des Experiments verfolgt und quantifiziert werden kann.